Gambaran Cabin Fever Pada Masa Pembelajaran Hybrid Mahasiswa Program Sarjana - Mahali, Nia Ainun Nadina; Sriati, Aat; Eriyani, Theresia; Hernawaty, Taty; Yulianita, Henny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the description of cabin fever during the hybrid learning period in undergraduate students at the Faculty of Nursing, Padjadjaran University. The research method used is descriptive quantitative. The population of this research is the 2019 and 2020 Faculty of Nursing Undergraduate Program Students with a total sample of 262 students. Sampling using total sampling technique. The results showed that the average score of cabin fever in nursing students at Padjadjaran University was (15 ± 12.44), which means that the level of cabin fever during the hybrid learning period was less than the average score of 15 and it can be concluded that cabin fever among nursing students at Padjadjaran University during the hybrid learning period fall into the low category. Keywords: Cabin fever, Hybrid Learning, Nursing Students